The Impact of Teacher Phubbing on Elementary Students’ Learning Motivation in the Digital Era - Eko Supratono; Sri Nurhayati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2026)
This study aimed to examine the relationship between perceived teacher phubbing and learning motivation among elementary school students in the digital era. Teacher phubbing refers to teachers’ non-instructional attention to smartphones or digital devices during learning activities, which may reduce direct communication with students. This study used a quantitative correlational design involving 130 students from Grades IV, V, and VI, selected from a population of 180 students through purposive sampling. Data were collected using Likert-scale questionnaires measuring perceived teacher phubbing and learning motivation, supported by observation and documentation. Instrument testing showed that the questionnaire items were valid and reliable, with Cronbach’s alpha of .88. Data were analyzed using descriptive statistics and Pearson Product Moment correlation. The results showed that perceived teacher phubbing was at a moderate level, while students’ learning motivation was also moderate, with concentration and classroom participation identified as vulnerable aspects. Pearson correlation analysis revealed a negative and significant relationship between teacher phubbing and learning motivation, r(128) = -.598, p < .001, with a 95% confidence interval of [-.698, -.475]. The coefficient of determination indicated that 35.8% of the variance in learning motivation was statistically associated with perceived teacher phubbing. These findings indicate that teacher attention remains an important motivational resource in digital-era elementary classrooms. The study contributes to digital education research by positioning teacher phubbing as a professional and relational issue, not merely a technology-use problem.